Assessment of ichthyotoxicity and anthropogenic contamination in the surface waters of Kenting National Park, Taiwan - Chen, Te-Hao; Chen, Yi-Ling; Chen, Chia-Yang; Liu, Pi-Jen; Cheng, Jing-O; Ko, Fung-Chi (Environmental monitoring and assessment, 2015)
Millions of tourists visit Kenting National Park (KNP) in southern Taiwan every year, causing great amount of sewage discharges in this area. This study aimed to assess the impact of sewage on KNP surface waters using zebrafish embryo-larval bioassays combined with chemical analyses of pharmaceuticals and personal care products (PPCPs). Surface water samples were collected monthly from May to October in 2010. During the monthly bioassays, zebrafish embryos were exposed to the water samples for 144 h. Hatchability, embryonic heart rate, larval survival rate, and deformities were recorded. Larval swimming behavior was also digitally quantified at the end of exposure. Significant decreases in hatchability and larval survival rate were observed at all sites. Both hatchability and larval survival rate were negatively correlated with nitrite and ammonia concentrations in the water. The field water had little effect on embryonic heart rate and morphology. However, lower swimming speeds and activity levels were observed in the larvae, suggesting neurobehavioral toxicity of the surface waters. The general detection frequency of the 28 target PPCPs was 75 %. High levels of some PPCPs, particularly caffeine, N , N -diethyl-3-methylbenzamide (DEET), and nonylphenol, were measured in the water samples. Our results show that surface waters in KNP have been strongly impacted by human activities, resulting in lethal and behavioral toxicities in developing fish.